Matriks Leslie dan Aplikasinya dalam Memprediksi Jumlah dan Laju pertumbuhan Penduduk di Kota Makassar - Wahidah Sanusi; Sukarna; Nur Ridiawati (Jurusan Matematika FMIPA UNM, 2018)
Population growth is a matter of note, if the population growth is not controlled, it will be difficult for the government to make prosperity. In 2010, In the city of Makassar was recorded 1,339,374 people with a growth rate of 1.65 percent every year. This study aims to predict the number and rate of population growth in Makassar city in 2017 by using Leslie Matrix. The factors which influence the population growth are the fertilit rate, the survival rate, and the age range of the population. The steps taken to predict the number of population p for the next year with using Leslie Matrix are forming a vector column n (t) whose entry is the initial number of population every age class. The second step is obtain the value of n (t + p) which is the population number for the next year p than use the formula n ( t + P) = Ap n (t) with A is the Leslie Matrix. And the last step, specify the dominant eigen value. The results obtained in 2017 predicted a total of 749,090 inhabitants with eigen values λ1=1.01 indicates that growth tends to raise.